Quality of life and associated factors among patients with tuberculosis at the University of Lahore Teaching Hospital, Lahore. (Journal of Rashid Latif Medical College, 2022)
AbstractMethods: In 2019, cross-sectional research was carried out between April and June. a total of four hundred patients altogether were chosen. QOL was measured using the World Health Organization Quality-of-Life (WHOQOL-Bref) questionnaire. Potential predictors were examined using linear regression analysis, and variables were classified as statistically significant if their P value was below 0.05.Results The participants had a mean age of 38.04 ± 13.53 years; the percentage of patients with pulmonary TB (PTB) was 52.71% and 57.36% were male. Conclusion In contrast to earlier researches, this study showed that the patients' quality of life was comparatively low. Social domains were notably more affected than other domains. PTB and non-adherence indicated a negative correlation with every domain. Therefore. health care providers should stress patients' medication adherence.Keywords Quality of life · Tuberculosis · WHOQOL-Bref · Ethiopia